The concept integration and language adaptation (Eurasian Journal of Philology Science and Education, 2016)
In this article is considered concept definitions integration and his universal character as process and result. The current system of higher education with its own laws of development and operation is designed to form a human ability to actively participate in the processes taking place in rapidly changing circumstances, guided by the integration process of self-realization of the individual. In this aspect, the author examines the concept of «educational, linguistic integration» based on personal values and orientations of the surrounding society and gives the definition of these concepts.The authors stresses that integration in pedagogical science inextricably connected with surrounding socium, with its educational system which is called to create the integrative conditions of cognitive work, which promote to organization of entire world view by the way of values and out world norms.
Keywords: integration; language adaptation; socialization.